Stereoscopic three-dimensional visualization applied to multimodal brain images: clinical applications and a functional connectivity atlas - Rojas, Gonzalo M.; Gálvez, Marcelo; Vega Potler, Natan; Craddock, R. Cameron; Margulies, Daniel S.; Castellanos, F. Xavier; Milham, Michael P. (Frontiers in Neuroscience, 2014)
Effective visualization is central to the exploration and comprehension of brain imaging data. While MRI data are acquired in three-dimensional space, the methods for visualizing such data have rarely taken advantage of three-dimensional stereoscopic technologies. We present here results of stereoscopic visualization of clinical data, as well as an atlas of whole-brain functional connectivity. In comparison with traditional 3D rendering techniques, we demonstrate the utility of stereoscopic visualizations to provide an intuitive description of the exact location and the relative sizes of various brain landmarks, structures and lesions. In the case of resting state fMRI, stereoscopic 3D visualization facilitated comprehension of the anatomical position of complex large-scale functional connectivity patterns. Overall, stereoscopic visualization improves the intuitive visual comprehension of image contents, and brings increased dimensionality to visualization of traditional MRI data, as well as patterns of functional connectivity.